Strengthening Collaborative Governance in the Department of Transportation: Implementation and Enforcement Levies - Hermansyah Hermansyah; Siti Zubaidah; Jumroh Jumroh; Zahra Ahmadi (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, Indonesia, 2024)
This article explores the strengthening of collaborative governance within Indonesia's Department of Transportation, focusing on the implementation and enforcement of levies. It highlights the integration of diverse stakeholders, including government bodies, private sector entities, and civil society, to create a more effective levy management system. However, a lack of collaboration between the Palembang city government and the local community has hindered the effectiveness of levies. Key strategies for improvement include promoting transparency, shared decision-making, and the use of innovative technologies. The study underscores the importance of trust and accountability among stakeholders to enhance compliance and enforcement. In Palembang, the capital of South Sumatra Province, transportation and traffic management challenges necessitate the effective implementation of levies. Employing a qualitative approach through in-depth interviews, observations, and documentation, the research reveals that collaborative efforts between local governments, the private sector, and the community are essential, despite challenges such as limited resources and community resistance. The findings suggest that while collaborative governance can improve the effectiveness of levy enforcement, it requires commitment and active participation from all parties. Recommendations include enhancing human resource capacity, strengthening regulatory frameworks, and raising public awareness of the importance of levies for regional revenue. This study also aligns with the Sustainable Development Goals (SDGs), particularly in improving infrastructure, fostering sustainable cities (SDG 11), and promoting effective partnerships (SDG 17).